2001
DOI: 10.1074/jbc.m101565200
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure and Interaction with Basic and Acidic Fibroblast Growth Factor of a 3-kDa Human Platelet Factor-4 Fragment with Antiangiogenic Activity

Abstract: Platelet factor-4 is a protein belonging to the family of ELR-negative CXC chemokines which binds to fibroblast growth factor and inhibits its mitogenic activity. Platelet factor-4 also inhibits tumor growth by mechanisms involving antiangiogenesis. Antiangiogenic activity in vitro has also been shown for the 24-residue Cterminal fragment of the protein, which decreases the affinity between basic fibroblast growth factor and its cell-surface receptor. In this study, the preferential conformation of this fragme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 79 publications
1
34
0
Order By: Relevance
“…Because proteins often undergo conformational changes when they bind to other molecules or macromolecular structures, the decrease in flexibility of the ␤8/␤9 loop of aFGF upon 5-amino-2-NMS binding should probably be considered an additional unfavorable contribution of 5-amino-2-NMS to the conformational fitting of aFGF to its receptor binding site. Slight changes on this loop have been shown to deeply affect the specific mitogenic activity of aFGF (52). Hindered heparin binding and poor fitting onto its receptor may both account for the low mitogenesis inducing capacity of aFGF complexed with 5-amino-2-NMS.…”
Section: Discussionmentioning
confidence: 99%
“…Because proteins often undergo conformational changes when they bind to other molecules or macromolecular structures, the decrease in flexibility of the ␤8/␤9 loop of aFGF upon 5-amino-2-NMS binding should probably be considered an additional unfavorable contribution of 5-amino-2-NMS to the conformational fitting of aFGF to its receptor binding site. Slight changes on this loop have been shown to deeply affect the specific mitogenic activity of aFGF (52). Hindered heparin binding and poor fitting onto its receptor may both account for the low mitogenesis inducing capacity of aFGF complexed with 5-amino-2-NMS.…”
Section: Discussionmentioning
confidence: 99%
“…PF4 binds FGF1 [171] and FGF2 [170]. In endothelial cells, PF4 inhibits FGF2 interaction with HSPGs and FGFR1, FGF2 internalization and mitogenic activity [170].…”
Section: Cytokinesmentioning
confidence: 99%
“…Since then, 22 structurally-related members of the FGF family have been identified [8]. FGFs are pleiotropic factors acting on different cell types, including www.elsevier.com/locate/cytogfr Cytokine & Growth Factor Reviews 16 (2005) [159][160][161][162][163][164][165][166][167][168][169][170][171][172][173][174][175][176][177][178] endothelial cells, following interaction with heparan-sulfate proteoglycans (HSPGs) and tyrosine kinase FGF receptors (FGFRs). To date, more than 1200 PubMed-referenced papers related to FGFs and FGFRs in endothelial cells and during neovascularization have been published.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, CXCL4/PF-4 inhibits epidermal growth factorstimulated proliferation of endothelial cells and interferes with the cell cycle by impaired downregulation of p21 CIP1/WAF1 (43). Further, it has been shown that different CXCL4/PF-4 peptides compete with FGF-2 or VEGF by inhibiting their binding to FGF or VEGF receptors, respectively, or reduce heparin-induced FGF-2 dimerization, resulting in the angiostatic activity (21,31,44,45). However, other mechanisms seem to be involved as well because an analogue of CXCL4/PF-4 that lacks affinity for heparin still retains its angiostatic activity (46), and CXCL4/PF-4 also inhibits the function of VEGF-121, an isoform with deficient heparin-binding ability (47).…”
Section: Discussionmentioning
confidence: 99%